12.12: Influence of welding on mechanical properties of high strength steel butt joints. (13th September 2017) - Chen, Cheng; Zhao, Ming‐Shan; Fung, Tat‐Ching; Chiew, Sing‐Ping; Lee, Chi‐King
ABSTRACT: In view of the fact that welding thermal cycle could adversely affect the mechanical properties of heat affected zone (HAZ) for quenched and tempered (QT) high strength steel (HSS) due to the transformation of microstructures, experiments were conducted to find out the correlation of welding heat input, hardness, microstructure and the tensile strength of HSS butt joints. Two S690 QT HSS butt joints were welded with 8mm thickness plates by shielded metal arc welding (SMAW), and 3.2mm and 5.0mm diameter electrodes were employed to achieve the conditions of different heat inputs. During welding, the thermal cycles near the weld bead were recorded by thermocouples. After the welding, the test specimens were cut out from the welded joints. Then, coupon tests were carried out to measure the tensile strength of joints. In addition, hardness tests and microstructure observation of HAZ on the well‐polished specimens were conducted. The test results reveal that a soft layer was generated in the fine grain heat affected zone (FGHAZ) with a lower hardness value. Eventually, it affects tensile strength of S690 QT HSS to some extents. Additionally, it was also found that increase of heat input leads to longer cooling time and consequently higher degree of HAZ softening.